المنـــاخ التنظيمــي وعلاقتــه بالأداء الوظيفــــي - علال, حسيبة; سعيد, خديجة (University of Eloued جامعة الوادي, 2023)
ملخص الدراسة تهدف هذه الدراسة إلى التعرف على طبيعة العلاقة بين المناخ التنظيمي والأداء والوظيفي لدى العمال الإداريين ببلدية الدبيلة ولاية الوادي، فانطلقت من التساؤل الرئيسي الآتي: ما علاقة المناخ التنظيمي بالأداء الوظيفي لدى العمال الإداريين ببلدية الدبيلة؟ وتندرج تحت هذا التساؤل الرئيسي تساؤلات فرعية وهي: *ما علاقة حوافز العمل بكفاءة العاملين لدى العمال الإداريين ببلدية الدبيلة؟ *هل يساهم النمط القيادي التشاركي في تحقيق الإبداع الوظيفي لدى العمال الإداريين ببلدية الدبيلة؟ *هل توجد علاقة بين نمط الاتصال المفتوح والالتزام الوظيفي لدى العمال الإداريين ببلدية الدبيلة؟ ولقد تم الاعتماد في هذه الدراسة على المنهج الوصفي يتماشى مع طبيعة الموضوع، كما تم تطبيق الاستمارة كأداة لجمع بيانات الدراسة، على عينة عشوائية بسيطة حصصية على (40) مفردة ولقد أسفرت على النتائج التالية: *توجد علاقة بين الحوافز العمل وكفاءة العاملين لدى العمال الإداريين ببلدية الدبيلة. *توجد علاقة بين نمط القيادة وتحقيق الإبداع الوظيفي لدى العمال الإداريين ببلدية الدبيلة. *توجد علاقة بين نمط الاتصال والالتزام الوظيفي لدى العمال الإداريين ببلدية الدبيلة. Summary of the study This study aims to identify the nature of the relationship between the organizational climate and job performance of administrative workers in the municipality of Al -Dabila, Eloued state. We have started from this main question: What is the relationship of the organizational climate to the job performance of administrative workers in the municipality of Al -Dabila? Sub-questions fall under this main question : *What is the relationship between incentives for work and the efficiency of workers among administrative workers in the municipality of Al -Dabila? *Does the participatory leadership pattern contribute to achieving career creativity among administrative workers in the municipality of Dabila? *Is there a relationship between the open communication pattern and the career commitment of administrative workers in the municipality of Dabila? In this study, the descriptive approach was relied upon in line with the nature of the subject, and the questionnaire was applied as a tool for collecting study data, on a simple random sample quota of (40) single individuals, and it yielded the following results: * There is a relationship between work incentives and employee efficiency among administrative workers in the municipality of Debeila. * There is a relationship between the leadership style and the achievement of job creativity among the administrative workers in the municipality of Debeila. * There is a relationship between communication style and job commitment among administrative workers in the municipality of Debeila.
دراســـــــة ميدانيـــــــة على عينــــــة عمـــال الإداريين لبلديــــــــــــــة - الدبيلــــــــــة -
مذكرة ماستر في علم الاجتماع تخصص تنظيم وعمل
Keywords: المناخ التنظيمي، le climat organisationnel, Organizational climate; الأداء الوظيفي، Fonctionnalité, Functionality